516 Children are walking! Innovative study of travel patterns and safety. (1st September 2016) - Levi, Sharon; Zaidel, David; Gitelman, Victoria; Prihed, Ido; Silbinger, Orly
Abstract : Background: An increasing interest in the lifestyle and active mobility of children and continuing concern for their travel safety and secure environment requires detailed information about trip patterns and activities. There is little research on travel patterns of children, in particular during leisure hours. This study was designed to demonstrate child travel patterns and safety in Israel utilising advanced trip survey tools and methods. Methods: Phase 1 included a national self-report internet based travel survey as well as an innovative GPS based travel survey and follow up CAPI interview in Jerusalem with children age 6–12. Phase 2 included an in-depth study of pedestrian behaviour based on video analysis at major intersections and GPS based travel survey using cellular phones in three cities in central Israel. Results: The findings indicate that walking is the most common mode of travel and children in Israel walk at a higher rate than their counterparts in other developed countries. The results include distances travelled, travel purposes and destinations, and differences among population groups. The study points to a number of risk-taking behaviours, including: dangerous walking while accompanied by an adult; vehicles not yielding to children at crosswalks; bicycling on roads and without helmets from a young age; and lack of safe pedestrian walkways. Conclusions: It is important to increase active mobility as part of a healthy lifestyle, however more efforts are needed to determine dangers to child pedestrians and promote safe walking. The study demonstrated feasibility of a GPS tracking method as well as the ability to obtain reliable activity and trip information from children as young as six years. The GIS spatial analysis provides an interesting and new perspective on child mobility and can influence both urban design and public health programming by identifying specific areas for behavioural and environmental treatment.